Management of claw horn lesions; a practitioner's guide through the literature. (2nd January 2019) - Newsome, Reuben; Reilly, Beth; Reader, Jon
Abstract : The authors of this article are members of the Cattle Lameness Academy, part of Synergy Farm Health, a veterinary practice covering Dorset, Somerset and East Devon. Following on from a recent and comprehensive review of foot trimming technique (Manning et al, 2016 ), the current authors were invited to discuss the evidence base for current foot trimming interventions, claw horn lesion treatments and specifically how these can inform clinical practice. The evidence pertaining to claw horn lesion treatments was reviewed byPotterton et al (2012) although several key studies have been published since. Additionally, a recent review of how statistics have improved our understanding of the lameness disease process has also been published (Randall et al, 2018a ). The purpose of the current article is therefore to provide the practitioner with a guide through key pieces of literature, highlight the problems that arise from gaps in the literature and discuss the methods that we can adopt to manage lameness when the reviewed literature is scarce.